2021
DOI: 10.1016/j.actamat.2020.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting functional degradation in NiTi shape memory alloys containing amorphous regions via atomistic simulations

Abstract: Molecular dynamics simulations are performed to provide a detailed understanding of the functional degradation of nano-scaled NiTi shape memory alloys containing amorphous regions. The origin of the experimentally reported accumulation of plastic deformation and the anomalous sudden increase of the residual strain under cyclic mechanical loading are explained by detailed insights into the relevant atomistic processes. Our work reveals that the mechanical response of shape-memory-alloy pillars under cyclic comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The polyhedral template matching method [54] implemented in OVITO [55] was used to visualize the occurrence of the martensitic phase transformation in the SMA matrix. It was confirmed [31,33] that this method well distinguishes the bcc-like ordered B2 (austenite) and the monoclinic B19' (martensite) structures. Based on this method, the blue, red and gray atoms depicted in the figures of the atomic configurations represent austenite, martensite, and undetermined structures (such as grain boundaries, wire-matrix interface, amorphous region, and thermal noise).…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The polyhedral template matching method [54] implemented in OVITO [55] was used to visualize the occurrence of the martensitic phase transformation in the SMA matrix. It was confirmed [31,33] that this method well distinguishes the bcc-like ordered B2 (austenite) and the monoclinic B19' (martensite) structures. Based on this method, the blue, red and gray atoms depicted in the figures of the atomic configurations represent austenite, martensite, and undetermined structures (such as grain boundaries, wire-matrix interface, amorphous region, and thermal noise).…”
Section: Methodsmentioning
confidence: 75%
“…MD simulations are very versatile and can provide a detailed understanding of the underlying mechanisms at the microscopic scale, if a reliable interatomic potential is available. For example, the martensitic transformation of NiTi SMAs has been successfully analyzed by performing MD simulations [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] using a reliable interatomic potential for the binary Ni-Ti system [45]. However, since no interatomic potential for the Nb-Ni-Ti ternary system is available yet, we have developed a new potential based on the second nearest-neighbor modified embedded-atom method (2NN MEAM) [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…In such scenarios, atomistic simulation techniques, such as density functional theory (DFT) calculations and molecular dynamics (MD), could well support the experimental observations and even discover new attributes and their origins. For instance, numerous investigations employing large-scale MD simulations have effectively revealed origins to several phenomena [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. For an MD simulation, an interatomic potential for the system of interest is essential, but the performance of the potential is another crucial aspect that is dependent on the model it is based on and the parameter fitting.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the accumulation of plastic deformation is caused by the interface migration and dislocation slip of martensite variants. The main factors of the superelastic degradation observed by Ko et al [ 25 ] under cyclic loading were the accumulated plastic deformation and the residual martensites present, which originated from the synergistic effect of the amorphous and crystalline regions. Due to the presence of the amorphous phase, increases in the stability of the martensite phase cause a sudden decrease in the stress plateau and hysteresis under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%